1979
DOI: 10.1093/infdis/139.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Respiratory Syncytial Virus in Nasal Secretions from Infants by Enzyme-Linked Immunosorbent Assay

Abstract: An enzyme-linked immunosorbent assay (ELISA) was developed for detection of respiratory syncytial virus (RSV) in nasal secretions from infants with respiratory disease. RSV was detected in 23 of 29 secretions positive for RSV by tissue culture and in one of 36 samples negative for RSV by tissue culture. The ELISA was a simple rapid, and surprisingly sensitive test for identification of RSV infection in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 9 publications
2
41
0
2
Order By: Relevance
“…The results of the present and earlier studies (Sarkkinen et al, 1981 a, b), and the results of other groups (Chao et al, 1979;Berg et aL, 1980) indicate that at least adenovirus, influenza A and B virus, parainfluenza types 1, 2 and 3, and respiratory syncytial virus antigens can be detected directly from the nasopharyngeal specimens of patients with acute respiratory infection.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results of the present and earlier studies (Sarkkinen et al, 1981 a, b), and the results of other groups (Chao et al, 1979;Berg et aL, 1980) indicate that at least adenovirus, influenza A and B virus, parainfluenza types 1, 2 and 3, and respiratory syncytial virus antigens can be detected directly from the nasopharyngeal specimens of patients with acute respiratory infection.…”
Section: Discussionsupporting
confidence: 79%
“…Solid-phase enzyme-immunoassay (EIA) and radioimmunoassay (RIA) methods offer an alternative way of detecting viral antigens from clinical specimens and have been applied with great success in the detection of gastroenteritis viruses (Yolken et al, 1977;Sarkkinen et al, 1979;Halonen et al, 1980) and hepatitis A and B viruses (Purcell et al, 1973;Mathiesen et al, 1978). The recent work done in our laboratory (Sarkkinen et al, 1981 a, b) and in other laboratories (Chao et al, 1979;Berg et al, 1980) has indicated that the solid-phase immunoassays can be applied also in the detection of respiratory viruses as well. In the present study solid-phase EIA and RIA methods were applied for the detection of parainfluenza type 1, 2 and 3 virus antigens.…”
Section: Introductionmentioning
confidence: 88%
“…Latent viruses, such as HSVs and CMV, are commonly reactivated and may produce chronic infections (40,108,109). Adenovirus infections also become prolonged and may result in serious disease (54,116 (58) and enzyme immunoassay (EIA) (8,16,85,86,114). More recently, the shell vial technique, which was originally described for the rapid identification of CMV (27), has been used for the diagnosis of respiratory viruses (18,49,57,69,78,89 (94), and one study observed greater than 35% mixed infections in patients with viral infections (112); the total number of positive specimens in these studies was small, 21 and 17, respectively.…”
Section: Mixed Viral Infections In Immunodeficient Patientsmentioning
confidence: 99%
“…Sensitive ELISAs have been developed for detection of Haemophilus influenzae (11,37,145), Streptococcus pneumoniae (62,145), and Neisseria meningitidis (145) antigens in clinical specimens, using polyclonal or monoclonal antibodies. Various enzyme immunoassays have also been developed for detection of viral and bacterial antigens in respiratory secretions (2,27,101,171), cerebrospinal fluid (152), and endocervical and urethral specimens (122,152). Rapid diagnosis of respiratory syncytial virus in nasal secretions from infants and young children by ELISA has been carried out by several laboratories (19,63,72).…”
Section: Detection Of B Pertussis Antigensmentioning
confidence: 99%